For the Renowal Theology of Sacramnetal Priesthood - Tatar, Marek Jan (Studia Warmińskie, 2020)
The sacrament of priesthood within the whole space of the development of the Church and its presence in civilisation is one of the key issues. It proves its meaning as well as the necessity of undertaking an ongoing reflection in the context of challenges resulting from the civilisation development. Theology of priesthood is also an essential aspect that has a multi-dimension character and, as such, is a subject of various fields of theology as well as non-theological ones. A reflection upon its relation to a common priesthood of all the faithful, resulting from the sacrament of Baptism, comes into special importance nowadays. Present-day challenges resulting from the development of culture post-modernity require a clear and precise drawing of the essence of sacramental priesthood. The Sacrament of Orders which defines the character and charisma of the called one brings the inseparable sacramental bond with the Christ the Highest and the Only Patriarch. We can find a proper charismatic identity of priesthood in this relation. The other dimension of this charisma is the mission, in which a priest acts in persona Christi. The dual charismatic dimension makes a proper way of making out and understanding the identity of a priest. It means that a priest cannot be substituted in his vocation and the authority which he receives in The Sacrament of Holy Orders and the unity with his bishop. Properly understood and made out identity needs the competent preparation and formation of the candidates to the priesthood, those who have already received Orders and those who are responsible for it alike. All dimensions of formation must be properly integrated. The essential integrating element in the process of ongoing formation is specific priestly spirituality. It means that the fact who a priest is, and then what his mission is, results from the unity of a priest with Christ. The already mentioned civilisation challenges require permanent studies of the ways and methods of the formation. This way the process of formation defends itself from naturalistic or spiritualistic one-sidedness, which a present Pope Francis reminded of, when he said about two “subtle enemies of sanctity”, which are “a present-day Gnosticism” and “a present-day Pelagianism".